Preparation method of carbon fiber composite material

By using phosphate diazepaneone flame retardant in carbon fiber composite materials to react with carbon oxide fiber, the problem of poor flame retardant performance of carbon fiber epoxy resin composite materials is solved, and the material is efficient flame retardant, enhanced tensile strength and high temperature resistance are improved.

CN119877275AActive Publication Date: 2025-04-25SHANDONG TRILLION SPORTS HEALTH SERVICE CO LTD +1

Patent Information

Application Number
CN202510368653.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-27
Publication Date
2025-04-25
Estimated Expiration
2045-03-27

AI Technical Summary

Technical Problem

The flame retardant properties of carbon fiber epoxy resin composites are poor.

Method used

The phosphate diazepaneone flame retardant is used to react with carbon oxide fibers, and the flame retardant is attached to the surface of the carbon fibers through hydrogen bond interaction, and cured with the epoxy resin to form a nitrogen-phosphorus flame retardant system.

Benefits of technology

The flame retardancy, tensile strength and high temperature resistance of carbon fiber composites have been significantly improved, and the ultimate oxygen index and UL94 test grade have also been improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_2
    Figure SMS_2
  • Figure QLYQS_1
    Figure QLYQS_1
Patent Text Reader

Abstract

The invention relates to the technical field of carbon fiber composite materials, and discloses a preparation method of a carbon fiber composite material, the carbon fiber composite material comprises 5-20 parts by weight of oxidized carbon fiber, 3-15 parts by weight of phosphate phthalazinone flame retardant, 100 parts by weight of epoxy resin, 2.8-3.5 parts by weight of curing agent and the like. The phosphate phthalazinone flame retardant contains carboxyl, and can form hydrogen bond interaction force with hydroxyl, carboxyl and the like on the surface of the oxidized carbon fiber, so that the phosphate phthalazinone flame retardant is attached and modified on the surface of the oxidized carbon fiber, the dispersity of the carbon fiber becomes good, the compatibility between the carbon fiber and epoxy resin becomes good, and the tensile strength and high temperature resistance of the material are improved. The phosphate phthalazinone flame retardant contains a phosphate flame-retardant group and a nitrogen-containing heterocyclic ring, so that a nitrogen-phosphorus flame-retardant system is formed, and the flame retardance of the epoxy resin material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of carbon fiber composite materials, and in particular to a method for preparing a carbon fiber composite material. Background Art

[0002] Carbon fiber is an inorganic fiber material with excellent comprehensive performance, light weight, high mechanical strength, large modulus, and strong high temperature resistance. It is widely used in polymer materials such as epoxy resin, acrylic resin, polyethylene, and polypropylene. Chinese patent CN110734537B discloses a latent halogen-free flame-retardant epoxy resin curing agent, epoxy resin prepreg, and carbon fiber composite material. A phenolic hydroxyl aromatic aldehyde, amino imidazole, and DOPO are reacted to obtain a latent and halogen-free flame-retardant curing agent, so that the composite material of epoxy resin and carbon fiber has excellent mechanical properties and flame retardancy. In order to improve the compatibility between carbon fiber and polymer resin, it is usually necessary to modify the surface of carbon fiber. After the carbon fiber is oxidized by sulfuric acid, nitric acid, hydrogen peroxide, etc., oxygen-containing functional groups such as hydroxyl and carboxyl can be introduced on the surface, and further coated and reacted with polyaniline, silane coupling agent, titanate coupling agent, etc. to obtain functional carbon fiber, which can more effectively improve the mechanical and high temperature resistance properties of resin materials. Summary of the invention

[0003] The invention solves the problem that the carbon fiber epoxy resin composite material has poor flame retardancy and other properties.

[0004] Technical solution of the present invention: A method for preparing a carbon fiber composite material: (1) Add 5-20 parts by weight of oxidized carbon fiber to ethanol, disperse it by ultrasonication, then add 3-15 parts by weight of phosphate diazonium flame retardant, stir and remove ethanol by rotary evaporation, add the mixture to 100 parts by weight of epoxy resin, then add 0.4-0.8 parts by weight of polyether modified silicone defoamer and 2.8-3.5 parts by weight of curing agent 2-ethyl-4-methylimidazole, stir and cast it into a mold, vacuum degas, heat cure and demold to obtain a carbon fiber composite material.

[0005] Preferably, the heat curing conditions are first curing at 80-90° C. for 2-3 h, and then curing at 120-130° C. for 1.5-2 h.

[0006] Preferably, the preparation method of oxidized carbon fiber is: adding carbon fiber to concentrated sulfuric acid and concentrated nitric acid, ultrasonically dispersing, heating to 90-100°C, condensing and refluxing for 18-24 hours, pouring the solution into water to dilute, filtering, washing with sodium carbonate solution and water in turn, and drying to obtain oxidized carbon fiber.

[0007] Preferably, the preparation method of the phosphate diazonium ketone flame retardant is: add 4-(4-hydroxyphenyl)-2,3-diazinium-1-one, 3-bromo-2-(bromomethyl)propionic acid, and sodium carbonate to acetonitrile, heat to 55-70°C, react for 18-24 hours, remove acetonitrile by rotary evaporation, wash with hydrochloric acid solution and water in turn, separate the product by silica gel column chromatography, and the eluent is ethyl acetate and petroleum ether solution to obtain a diazinium ketone precursor.

[0008] (2) Add diazonium phthalide precursor, 5,5-dimethyl-2-chloro-1,3,2-dioxaphosphahexanoyl phosphate and triethylamine to dichloromethane, react at 20-25°C for 12-18 hours, remove dichloromethane by rotary evaporation, separate the product by silica gel column chromatography, and use ethyl acetate and petroleum ether solution as eluent to obtain phosphate diazonium phthalide flame retardant. The reaction formula is as follows: .

[0009] Preferably, the molar ratio of 4-(4-hydroxyphenyl)-2,3-naphthyridin-1-one, 3-bromo-2-(bromomethyl)propionic acid and potassium carbonate in (1) is (2-2.4):1 (2.6-3.4).

[0010] Preferably, the molar ratio of the diazonium phthalide precursor, 5,5-dimethyl-2-chloro-1,3,2-dioxaphosphahexanoyl phosphate and triethylamine in (2) is 1:(2-2.2):(2-2.2).

[0011] The beneficial technical effect of the present invention is as follows: the phosphate phthalazinone flame retardant prepared by the present invention contains a carboxyl group, which can form a hydrogen bond interaction force with the hydroxyl group, carboxyl group, etc. on the surface of the oxidized carbon fiber during the stirring and mixing process, so that the phosphate phthalazinone flame retardant is attached and modified on the surface of the oxidized carbon fiber. After the flame retardant is organically modified, the dispersion of the carbon fiber is improved, and when added to the epoxy resin, the compatibility with the epoxy resin is improved, so that the carbon fiber has a better reinforcement effect and the tensile strength of the material is improved. At the same time, the oxidized carbon fiber is evenly dispersed in the epoxy resin, and the thermal decomposition temperature and high temperature resistance of the composite material are also improved.

[0012] The phosphate phthalazinone flame retardant of the present invention contains a phosphate flame retardant group and a nitrogen-containing heterocycle to form a nitrogen-phosphorus flame retardant system, which improves the charring property of the epoxy resin material during combustion, improves the limiting oxygen index of the composite material, and reaches the level of V1 to V0 in the UL94 test, thereby improving the flame retardancy.

[0013] In the high-temperature thermal curing process of the present invention, the carboxyl group contained in the phosphate diazonium ketone flame retardant can undergo a curing reaction with the epoxy resin, thereby introducing the heat-resistant diazonium ketone barrier structure into the epoxy resin molecular chain, which can further improve the high-temperature resistance and thermal decomposition temperature of the material. In addition, as a reactive flame retardant, the phosphate diazonium ketone flame retardant will not have a negative impact on the mechanical properties of the epoxy resin. DETAILED DESCRIPTION

[0014] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0015] The epoxy resin model is bisphenol A epoxy resin E44. Carbon fiber, average fineness 7um. Polyether modified silicone defoamer model is DT-698.

[0016] The CAS registration number of 4-(4-hydroxyphenyl)-2,3-naphthyridin-1-one is 152594-70-2. The CAS registration number of 3-bromo-2-(bromomethyl)propionic acid is 41459-42-1. The CAS registration number of 5,5-dimethyl-2-chloro-1,3,2-dioxaphosphahexanalactone phosphate is 4090-55-5.

[0017] Embodiment 1: (1) Add 20 g of carbon fiber to 450 mL of concentrated sulfuric acid (mass fraction 98%) and 150 mL of concentrated nitric acid (mass fraction 70%), ultrasonically disperse for 2 h, heat to 90 °C, condense and reflux for 24 h, pour the solution into water for dilution, filter, wash with sodium carbonate solution and water in turn, and dry to obtain oxidized carbon fiber.

[0018] (2) Add 0.2 mol of 4-(4-hydroxyphenyl)-2,3-naphthyridin-1-one, 0.1 mol of 3-bromo-2-(bromomethyl)propionic acid and 0.68 mol of sodium carbonate to 700 mL of acetonitrile, heat to 70°C, react for 18 h, remove acetonitrile by rotary evaporation, wash with hydrochloric acid solution and water in sequence, separate the product by silica gel column chromatography, eluents are ethyl acetate and petroleum ether solution, and obtain a naphthyridin-1-one precursor.

[0019] (3) Add 0.2 mol of a phthalazinone precursor, 0.4 mol of 5,5-dimethyl-2-chloro-1,3,2-dioxaphosphahexanoyl phosphate and 0.4 mol of triethylamine to 1 L of dichloromethane, and react at 20°C for 18 h. Remove the dichloromethane by rotary evaporation, and separate the product by silica gel column chromatography. The eluent is ethyl acetate and petroleum ether solution, to obtain a phosphate phthalazinone flame retardant.

[0020] (4) Add 50 g of oxidized carbon fiber to ethanol and disperse it by ultrasonication for 2 h. Then add 30 g of phosphate diazonium flame retardant. After stirring, remove the ethanol by rotary evaporation. Add the mixture to 1 kg of epoxy resin. Then add 5 g of polyether modified silicone defoamer and 30 g of curing agent 2-ethyl-4-methylimidazole. After stirring, cast it into a mold, vacuum degas, first heat cure at 90 °C for 2 h, then heat cure at 130 °C for 1.5 h, and demold to obtain a carbon fiber composite material.

[0021] Embodiment 2: (1) Add 20 g of carbon fiber to 450 mL of concentrated sulfuric acid (mass fraction 98%) and 150 mL of concentrated nitric acid (mass fraction 70%), ultrasonically disperse for 2 h, heat to 100 °C, condense and reflux for 18 h, pour the solution into water for dilution, filter, wash with sodium carbonate solution and water in turn, and dry to obtain oxidized carbon fiber.

[0022] (2) Add 0.24 mol of 4-(4-hydroxyphenyl)-2,3-naphthyridin-1-one, 0.1 mol of 3-bromo-2-(bromomethyl)propionic acid and 0.52 mol of sodium carbonate to 800 mL of acetonitrile, heat to 55°C, react for 24 h, remove acetonitrile by rotary evaporation, wash with hydrochloric acid solution and water in turn, separate the product by silica gel column chromatography, eluents are ethyl acetate and petroleum ether solution, and obtain a naphthyridin-1-one precursor.

[0023] (3) Add 0.2 mol of a phthalazinone precursor, 0.44 mol of 5,5-dimethyl-2-chloro-1,3,2-dioxaphosphahexanoyl phosphate and 0.44 mol of triethylamine to 1 L of dichloromethane, and react at 25 °C for 12 h. Remove the dichloromethane by rotary evaporation, and separate the product by silica gel column chromatography. The eluent is ethyl acetate and petroleum ether solution to obtain a phosphate phthalazinone flame retardant.

[0024] (4) Add 100 g of oxidized carbon fiber to ethanol and disperse it by ultrasonication for 2 h. Then add 70 g of phosphate diazonium flame retardant. After stirring, remove the ethanol by rotary evaporation. Add the mixture to 1 kg of epoxy resin. Then add 4 g of polyether modified silicone defoamer and 35 g of curing agent 2-ethyl-4-methylimidazole. After stirring, cast it into a mold, vacuum degassing, first heat curing at 80 °C for 3 h, then heat curing at 120 °C for 2 h, and demolding to obtain a carbon fiber composite material.

[0025] Embodiment 3: (1) 150 g of oxidized carbon fiber was added to ethanol and dispersed by ultrasound for 2 h. Then, 110 g of phthalazinone phosphate flame retardant was added. After stirring, the ethanol was removed by rotary evaporation. The mixture was added to 1 kg of epoxy resin. Then, 8 g of polyether-modified silicone defoamer and 32 g of curing agent 2-ethyl-4-methylimidazole were added. After stirring, the mixture was cast into a mold, vacuum degassed, first heat cured at 90 °C for 2 h, then heat cured at 120 °C for 2 h, and demolded to obtain a carbon fiber composite material.

[0026] Embodiment 4: (1) 200 g of oxidized carbon fiber was added to ethanol and dispersed by ultrasonication for 2 h. Then, 150 g of phthalazinone phosphate flame retardant (prepared according to the method of Example 1) was added. After stirring, the ethanol was removed by rotary evaporation. The mixture was added to 1 kg of epoxy resin. Then, 5 g of polyether-modified silicone defoamer and 28 g of curing agent 2-ethyl-4-methylimidazole were added. After stirring, the mixture was cast into a mold, vacuum degassed, first heat-cured at 85 ° C for 3 h, then heat-cured at 120 ° C for 2 h, and demolded to obtain a carbon fiber composite material.

[0027] Comparative Example 1: (1) Add 5 g of polyether-modified silicone defoamer and 30 g of curing agent 2-ethyl-4-methylimidazole to 1 kg of epoxy resin, stir and cast into a mold, vacuum degass, first heat cure at 90 ° C for 2 h, then heat cure at 130 ° C for 1.5 h, demold, and obtain an epoxy resin material.

[0028] Comparative Example 2: (1) Add 50 g of oxidized carbon fiber, 5 g of polyether-modified silicone defoamer, and 30 g of curing agent 2-ethyl-4-methylimidazole to 1 kg of epoxy resin, stir and cast into a mold, vacuum degassing, first heat curing at 90 ° C for 2 h, then heat curing at 130 ° C for 1.5 h, demolding, and obtaining a carbon fiber composite material.

[0029] Comparative Example 3: (1) To 1 kg of epoxy resin, 30 g of a phosphate phthalazinone flame retardant (prepared according to the method of Example 1), 5 g of a polyether-modified silicone defoamer, and 30 g of a curing agent, 2-ethyl-4-methylimidazole, were added. The mixture was stirred and cast into a mold. Vacuum degassing was performed. The mixture was first heat-cured at 90° C. for 2 h and then heat-cured at 130° C. for 1.5 h. The epoxy resin material was demolded to obtain the epoxy resin material.

[0030] Comparative Example 4: (1) Add 50 g of carbon fiber to ethanol and disperse it by ultrasonic for 2 h. Then add 30 g of phosphate diazonium flame retardant (prepared according to the method of Example 1). After stirring, remove the ethanol by rotary evaporation. Add the mixture to 1 kg of epoxy resin. Then add 5 g of polyether modified silicone defoamer and 30 g of curing agent 2-ethyl-4-methylimidazole. After stirring, cast it into a mold, vacuum degas, first heat cure at 90 ° C for 2 h, then heat cure at 130 ° C for 1.5 h, and demold to obtain a carbon fiber composite material.

[0031] Comparative Example 5 (1) Add 50 g of oxidized carbon fiber (prepared according to the method of Example 1) to ethanol and disperse it by ultrasound for 2 h. Then add 30 g of diazonium ketone precursor (prepared according to the method of Example 1) and remove the ethanol by rotary evaporation after stirring. Add the mixture to 1 kg of epoxy resin, and then add 5 g of polyether-modified silicone defoamer and 30 g of curing agent 2-ethyl-4-methylimidazole. After stirring, cast it into a mold, vacuum degas, first heat cure at 90°C for 2 h, then heat cure at 130°C for 1.5 h, and demold to obtain a carbon fiber composite material.

[0032] The tensile properties of epoxy resin casting materials are tested according to the national standard GB / T 2567-2021. The oxygen index is tested according to the national standard GB / T2406.1-2008. The vertical burning performance is tested according to the UL-94 method.

[0033] 5 mg of the casting material was weighed and thermal properties were tested in a thermogravimetric analyzer under a nitrogen atmosphere, with the temperature rising from 25° C. to 800° C. at a heating rate of 10° C. / min.

[0034] Table 1 Casting material performance test After testing, the epoxy resin material of Comparative Example 1 has low tensile strength, a limiting oxygen index of only 25.8%, no grade in the UL94 test, poor flame retardancy, and low initial thermal decomposition temperature (the temperature at which the mass loss is 5%) and residual carbon content, and poor high temperature resistance.

[0035] Oxidized carbon fiber and phosphate phthalazinone flame retardant are added to the composite material of Example 1-4. The flame retardant contains carboxyl groups. During the stirring and mixing process, hydrogen bond interaction forces can be formed with hydroxyl groups, carboxyl groups, etc. on the surface of the oxidized carbon fiber, so that the phosphate phthalazinone flame retardant is attached and modified on the surface of the oxidized carbon fiber. After the flame retardant is organically modified, the dispersion of the carbon fiber is improved, and the compatibility with the epoxy resin is improved, so that the reinforcement effect of the carbon fiber is improved, the tensile strength of the material is significantly increased, and the thermal decomposition temperature and high temperature resistance are also improved. The phosphate phthalazinone flame retardant contains phosphate flame retardant groups and nitrogen-containing heterocycles to form a nitrogen-phosphorus flame retardant system, which significantly improves the carbonization and flame retardancy of the epoxy resin material, improves the limiting oxygen index, and the UL94 test reaches the level of V1 to V0. During the high-temperature thermal curing process, the carboxyl group contained in the phosphate diazonium ketone flame retardant can undergo a curing reaction with the epoxy resin, thereby introducing the heat-resistant diazonium ketone flame retardant structure into the epoxy resin molecular chain, which can further improve the high-temperature resistance of the material and exhibit a higher thermal decomposition temperature.

[0036] Compared with Example 1, Comparative Example 2 only added oxidized carbon fiber, which has poor dispersibility and poor compatibility with epoxy resin. The improvement in the tensile strength of the material is not significant, and the limiting oxygen index is only 26.3%. There is no grade in the UL94 test and the flame retardancy is poor.

[0037] In comparative example 3, only phosphate phthalazinone flame retardant is added, and the flame retardancy of the material is significantly improved. In the high-temperature thermal curing process, the carboxyl group of the flame retardant can undergo a curing reaction with the epoxy resin, thereby introducing the heat-resistant phthalazinone barrier structure into the epoxy resin molecular chain, which can improve the thermal decomposition temperature and high temperature resistance of the material. The initial thermal decomposition temperature and residual carbon content are higher than those in comparative example 1, and as a reactive flame retardant, it has almost no effect on the mechanical properties of the epoxy resin. Good tensile strength is still maintained. However, without the addition of carbon fiber, the mechanical strength is low.

[0038] The carbon fiber added in Comparative Example 4 has not been subjected to mixed acid oxidation, and does not contain functional groups such as hydroxyl and carboxyl groups on the surface. It cannot form hydrogen bond interaction forces with the carboxyl groups of the phosphate diazonium phthalide flame retardant, and the flame retardant cannot be attached and modified on the surface of the oxidized carbon fiber. The organic modification of the carbon fiber cannot be achieved, the dispersibility of the carbon fiber cannot be improved, and the compatibility with the epoxy resin cannot be improved, resulting in poor reinforcement effect of the carbon fiber and the tensile strength of the material is lower than that of Example 1.

[0039] The diazonium precursor added in Comparative Example 5 contains a carboxyl group, which can form a hydrogen bond interaction force with the hydroxyl group, carboxyl group, etc. on the surface of the oxidized carbon fiber, thereby attaching and modifying the phosphate diazonium flame retardant on the surface of the oxidized carbon fiber. After the organic modification of the flame retardant, the dispersibility of the carbon fiber is improved, and at the same time, the compatibility with the epoxy resin is improved, the reinforcement effect of the carbon fiber is improved, and the tensile strength of the material is significantly increased. However, the diazonium precursor does not contain a phosphate flame retardant group, and the flame retardancy of the material is poor.

[0040] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

Claims

1. A method for preparing a carbon fiber composite material, characterized in that: The preparation method is as follows: (1) Add 5-20 parts by weight of oxidized carbon fiber to ethanol, disperse it by ultrasonication, then add 3-15 parts by weight of phosphate diazonium flame retardant, stir and remove ethanol by rotary evaporation, add the mixture to 100 parts by weight of epoxy resin, then add 0.4-0.8 parts by weight of defoamer and 2.8-3.5 parts by weight of curing agent, stir and cast it into a mold, vacuum degas, heat cure, and demold to obtain a carbon fiber composite material; The structural formula of the phosphate phthalazinone flame retardant is: 。 2. The method for preparing a carbon fiber composite material according to claim 1, characterized in that: The curing agent is 2-ethyl-4-methylimidazole, and the defoaming agent is a polyether-modified organic silicon defoaming agent.

3. The method for preparing a carbon fiber composite material according to claim 1, characterized in that: The heat curing conditions are: first curing at 80-90° C. for 2-3 hours, and then curing at 120-130° C. for 1.5-2 hours.

4. The method for preparing a carbon fiber composite material according to claim 1, characterized in that: The preparation method of the oxidized carbon fiber is as follows: adding the carbon fiber to concentrated sulfuric acid and concentrated nitric acid, ultrasonically dispersing, heating to 90-100° C., condensing and refluxing for 18-24 hours, pouring the solution into water for dilution, filtering, washing, and drying to obtain the oxidized carbon fiber.

5. The method for preparing a carbon fiber composite material according to claim 1, characterized in that: The preparation method of the phosphate phthalazinone flame retardant is: (1) Add 4-(4-hydroxyphenyl)-2,3-naphthyridin-1-one, 3-bromo-2-(bromomethyl)propionic acid and sodium carbonate to acetonitrile, heat to 55-70°C, react for 18-24 hours, rotary evaporate, wash, and separate by silica gel column chromatography to obtain a naphthyridinone precursor; (2) Add a phthalazinone precursor, 5,5-dimethyl-2-chloro-1,3,2-dioxaphosphahexanoyl phosphate and triethylamine to dichloromethane, react at 20-25° C. for 12-18 hours, rotary evaporate, and separate by silica gel column chromatography to obtain a phosphate phthalazinone flame retardant.

6. The method for preparing a carbon fiber composite material according to claim 5, characterized in that: The molar ratio of 4-(4-hydroxyphenyl)-2,3-naphthyridin-1-one, 3-bromo-2-(bromomethyl)propionic acid and potassium carbonate in (1) is (2-2.4):1 (2.6-3.4).

7. The method for preparing a carbon fiber composite material according to claim 5, characterized in that: The molar ratio of the diazonium phthalide precursor, 5,5-dimethyl-2-chloro-1,3,2-dioxaphosphahexanoyl phosphate and triethylamine in (2) is 1:(2-2.2):(2-2.2).

Citation Information

Patent Citations

  • A latent halogen-free flame-retardant epoxy resin curing agent, epoxy resin prepreg, and carbon fiber composite material

    CN110734537B

  • Flame-retardant and aging-resistant epoxy resin glass fiber reinforced plastic for shell of four-wheel electric vehicle

    CN108752872A

  • Hollow fiber membrane, preparation method thereof and dialyzer

    CN112705054A

  • Halogen-free flame-retardant polyurethane elastomer and preparation process

    CN118108924A

Cited By

  • Phosphorus-based eutectic solvent, modified epoxy resin, carbon fiber composite material and preparation method thereof

    CN121495084A